An Investigation into Linguistic Features of Sports Expressions Used Metaphorically and Idiomatically in Non-Sports Situations (English Versus Vietnamese) - Nguyễn Đức Tú (2011)
Sport is an indispensable part of our daily life. In the domain of sport, the use of expressions used metaphorically and idiomatically is quite common, the metaphors and idioms ….